2022
DOI: 10.1186/s12947-022-00287-0
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Doppler derived biphasic velocities during the pre and post-ejection phases: patterns, concordance and hemodynamic significance in health and disease

Abstract: Background Pre-(PRE) and post-ejection (POE) velocities by mitral annular tissue Doppler (TD) are biphasic and may be related to myocardial deformations. We investigated the predominance and concordance of TD-PRE and POE velocities and their effect on myocardial functions in controls and in heart failure (HF) patients. Methods Retrospectively, 84 HF patients [57.6 years, 28(33%) females, NYHA: 2.3 ± 0.6, EF: 55 ± 15%, 52(62%) preserved EF, and 32(3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Moreover, earlier experimental studies have shown that a rapid change in LV shape during IVC is essential for optimal onset of LV ejection. 4,5 This transient reshaping of LV geometry during IVC is registered on tissue Doppler imaging as biphasic longitudinal myocardial velocity spikes, 6,7 and IVCv is the positive component of those spikes. Therefore, it can be assumed that preservation of IVCv may be beneficial for LV systolic function in patients with HFpEF.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, earlier experimental studies have shown that a rapid change in LV shape during IVC is essential for optimal onset of LV ejection. 4,5 This transient reshaping of LV geometry during IVC is registered on tissue Doppler imaging as biphasic longitudinal myocardial velocity spikes, 6,7 and IVCv is the positive component of those spikes. Therefore, it can be assumed that preservation of IVCv may be beneficial for LV systolic function in patients with HFpEF.…”
Section: Introductionmentioning
confidence: 99%